Schering en inslag, samenwerken aan meer verwevenheid! Een verkennend onderzoek naar de haalbaarheid van een agglomeratie Twente-Münsterland - Bogaarts, René (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Grenzüberschreitende Kooperation; Münsterland; Münsterland (West); Twente

Papieren Hollanders. Werken met behoud van het Nederlandschap in 1892–1914 - Salemink, Theo (Van huis en haard. Migratie door de eeuwen heen, 2023)
Keywords: Achterhoek (Landschaft); Bocholt; Gendringen; Grenzarbeitnehmer

Fermeture des frontières nationales. Récits en territoire transfrontalier - Caesar, Beate; Dorkel, Nicolas; Marbehant, Sylvain; Rouchet, Hélène; Szendrei, Greta (Borders in Perspective UniGR-CBS Thematic Issue. Bordering in Pandemic Times: In- sights into the COVID-19 Lockdown, 2020)
Keywords: COVID-19; Grenzarbeitnehmer; Pandemie; Saar-Lor-Lux

Unternehmer mit niederländischen Wurzeln und niederländische Arbeiter auf der westmünsterländischen Seite der Baumwollstraße um 1900 - Freitag, Werner (Westfälische Forschungen, 2020)
Keywords: Ausländischer Arbeitnehmer; Grenzarbeitnehmer; Grenzgebiet; Münsterland (West); Niederländer; Textilindustrie; Unternehmen

Marché du travail transfrontalier. Négocier avec les frontères à l’heure de la crise sanitaire COVID-19 - Pigeron-Piroth, Isabelle; Evrard, Estelle; Belkacem, Rachid (Bordering in Pandemic Times. In- sights into the COVID-19 Lockdown, 2020)
Keywords: COVID-19; Grenzarbeitnehmer; Pandemie; Saar-Lor-Lux

Wonen en werken over de grens. Nederland - Duitsland - Bäumler, Robert; Pechholt, M. L. H. A.; Xhonneux, Heike (Wolters Kluwer, 2018)
Inhaltsverzeichnis: https://hbz-ulbms.primo.exlibrisgroup.com/permalink/49HBZ_ULM/7ca9dq/alma991026211049706449
Keywords: Grenzarbeitnehmer

Zo dicht bij elkaar, maar toch heel anders. Eigendomsverhoudingen, productie en werkgelegenheid in de vier mijnbouwgebieden in het Maas-Rijngebied - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2016)
Keywords: Arbeitsmarkt; Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Changing Border Regimes. Mining, and Cross-border Labor in the Dutch–Belgian–German Borderlands, 1900–1973 - Knotter, Ad (Journal of Borderlands Studies, 2014)
„In this article the incidence of cross-border commuting to the mining districts in the Belgian–Dutch–German borderlands, known today as the Euregion Meuse-Rhine, will be related to the impact of state borders in different periods. Cross-border labor was closely related to changing border regimes based on uneven economic development, (un)familiarity, and the policy impact of powerful institutions like the state and the church. The main argument is that after the First World War in Dutch Limburg a conscious policy to control the labor force and bind them to mining in the region was relatively successful. Discrepancies in wages and employment opportunities led to border-crossing during restricted periods and for specific groups of workers only.“
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

The impact of boundaries on cross-border mobility and migration in the Liège-Limburg area (19th–20th centuries) as retrieved from population records - Rutten, Willibrord (Internationales Archivsymposion in Luxemburg (2012). Grenzüberschreitende Migration und Archive. Annalen, mit einem Nachtrag zum Symposion Lüttich (2011) Erster Weltkrieg, 2013)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Buitenbeentjes. Nederlandse kompels in de Luikse kolenmijnen na de Tweede Wereldoorlog - Rutten, Willibrord (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2011)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau

Alsof de taalgrens niet bestond. Limburgse kompels in de Luikse kolenmijnen na de Tweede Wereldoorlog - Rutten, Willibrord (Het Land van Herle. Historisch tijdschrift voor oostelijk Zuid-Limburg, 2009)
Keywords: Grenzarbeitnehmer; Lüttich; Sprachgrenze; Steinkohlenbergbau; Südlimburg (Niederlande)

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)

Elastic Migration. The Case of Dutch Short-Distance Transmigrants in Belgian and German Borderlands - Houtum, Henk van; Gielis, Ruben (Tijdschrift voor Economische en Sociale Geografie, 2006)
Abstract: „Along the Dutch-Belgian and Dutch-German border a new and interesting kind of transmigration is developing, that is migration over only a few kilometres across the border. The main characteristic of these Dutch short-distance transmigrants is that they have their houses in Belgium/Germany, but their social and working life still takes place in the Netherlands. Their transmigration is hence very elastic. This elasticity invokes the interesting question: what kind of (trans)national identity these Dutch are displaying and to what extent the Dutch desire to be and/or are socially provoked to be integrated in the neighbouring Belgian/German society. These cross-border spaces in which the short-distance migrants have their residences could very well be interesting micro-scale laboratories of the future of the nation-state in the European Union.“
Keywords: Grenzarbeitnehmer; Mobilität; Sozialraum; Wohnungsmarkt

Trekarbeiders en pendelaars. Grensarbeid in oostelijk Zuid-Limburg, 1875–1914 - Langeweg, Serge (Zestig jaar vorsen in de geschiedenis. Jubileumboek Het Land van Herle 1945–2005, 2006)
Keywords: Arbeitsmigration; Grenzarbeitnehmer; Südlimburg (Niederlande)

Werk in de marge? Grensarbeid vanuit het Nederlandse naar het Duitse deel van de Euregio Maas-Rijn, 1960–2000 - Bouwens, Sophie (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2005)
Keywords: Euregio Maas-Rhein; Grenzarbeitnehmer; Südlimburg (Niederlande)

Spheres of Transnationalism within the European Union. On Open Doors, Thresholds and Drawbridges along the Dutch–German Border - Strüver, Anke (Journal of Ethnic and Migration Studies, 2005)
Abstract: „This article addresses the European Union's claim to establish transnational spaces through co-operation across its internal borders. Focusing on the Dutch–German borderland as an example, people's practices towards this border and their perceptions of it are introduced. It is underscored that these practices are influenced by popular representations, which (re)produce bounded spaces and the barrier effect of the border, thus making it difficult to imagine a transnational space. This observation is complemented by the phenomenon that—due to a housing shortage in the Netherlands—Dutch people have recently begun to move to German places directly on the border, although they maintain their jobs in the Netherlands. Concentrating specifically on one of these German villages, Kranenburg, the emergence of a community of transmigrants is highlighted in order to reflect upon the question of whether this form of frequent short-distance border crossing fosters a European transnational sphere.“
Keywords: Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Kranenburg (Kleve); Sozialraum; Transnationalisierung

Begrensde grenzeloosheid. Een FNV-nota over grensarbeid - Essers, Ger; Tasma, Eelco (Stichting FNV Pers, 2004)
Inhaltsverzeichnis: http://digitale-objekte.hbz-nrw.de/storage/2010/09/09/file_1/3888037.pdf
Keywords: Grenzarbeitnehmer

Historische interacties in de Euregio Maas-Rijn. Migratiestromen in een grensgebied - Korres, Achim (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer

Werken over de grens. Limburgers naar Duitsland, 1870–1914 - Langeweg, Serge (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmarkt; Arbeitsmigration; Deutschland; Grenzarbeitnehmer; Provinz Limburg (Niederlande)

Significant insignificance. Boundaries in a borderless European Union. Deconstructing the Dutch–German transnational labour market - Strüver, Anke (Journal of Borderlands Studies, 2002)
Abstract: „This contribution elaborates on European Union (E.U.) geopolitical discourses, which attempt to overcome the ‘insignificance’ of state‐borders through the establishment of cross‐border regions. Drawing on the nonexisting Dutch‐German transnational labor market as an example, the observed ‘non‐practice’ of border crossing is introduced. ‘Significant boundaries’ and their meanings, on the other hand, are constructed by narratives and images that are not only representations, but also actively shape people's everyday life. The effects of these boundary narratives are analyzed in terms of ‘cognitive distance’, defined both as the creation of a barrier effect and the ignorance of what lies beyond, expressed as a boundary in people's minds.“
Keywords: Arbeitsmarkt; Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Grenzüberschreitende Kooperation